Controlled synthesis of N, N-dimethylarylsulfonamide derivatives as nematicidal agents. Issue 12 (1st December 2020) - Chen, Gen-Qiang; Xia, Yan-Fei; Yang, Jin-Ming; Che, Zhi-Ping; Sun, Di; Li, Shen; Tian, Yue-E; Liu, Sheng-Ming; Jiang, Jia; Lin, Xiao-Min
Abstract: Gramine can be intelligently and efficiently supplied with N, N -dimethylamino group and then reacted with the corresponding sulfonyl chlorides to synthesize N, N -dimethylarylsulfonamides. We herein designed and controlled synthesis of N, N -dimethylarylsulfonamide derivatives, and first reported the results of the nematicidal activity of 15 title compounds 3a-o against Meloidogyne incongnita in vitro, respectively. Among all of the title derivatives, compounds 3a, 3c, 3k, and 3o exhibited potent nematicidal activity with median lethal concentration (LC50 ) values ranging from 0.22 to 0.26 mg/L. Most noteworthy, N, N -dimethyl-4-methoxyphenylsulfonamide (3c ) and N, N -dimethyl-8-quinolinesulfonamide (3o ) showed the best promising and pronounced nematicidal activity, with LC50 values of 0.2381 and 0.2259 mg/L, respectively. Graphical Abstract: